Study on the evolution law of the ‘Butterfly-type’ plastic zone in the surrounding rock of deep dynamic pressure roadway - Yiwen Liang; Jianqiang Jin; Wenhua Zha; Tao Xu; Wenbo Cheng (Scientific Reports)
Abstract The formation and development of plastic zone in the surrounding rock is the essence of large deformation damage to the surrounding rock in deep, highly stressed roadway. The −850 m roadway of the Qujiang mine is laid flat longitudinally under the 805 working face and coal pillar, and under the influence of the mining movement of the upper working face and the pre-stressing pressure of the coal pillar, the periphery of the roadway is no longer a pure non-uniform stress field, but a non-uniform stress field with both vertical and horizontal dynamic pressure. Based on the Hoek–Brown strength criterion, the unified strength theory is modified and the nonlinear unified strength theory of rock is established by comprehensively considering the intermediate principal stress, rock properties and rock structure. The boundary line equation of the plastic zone of the surrounding rock with non-uniform stress field under mining is proposed, and the effects of lateral pressure coefficient, Hoek–Brown parameter and intermediate principal stress as well as dynamic pressure coefficient on the morphology of the plastic zone are investigated. The results show that: (1) When the lateral pressure coefficient λ ≠ 1.0, the plastic zone of the surrounding rock expands in the direction of inclination to the corners of the roadway, and the whole is similar to the “butterfly-type”, and the more the value of λ deviates from l.0, the more the shape of the plastic zone is similar to the “butterfly-type”. (2) Regarding the dynamic pressure coefficient and the change curve of the radius of the plastic zone, whether it is the shallow stress field or the deep stress field, the curve is the first smooth growth, and the dynamic pressure coefficient reaches a certain value (about D i  = 2.5), and the radius of the plastic zone starts to show a sharp nonlinear growth, which is a ‘sharp lifting type’. The influence of the dynamic pressure coefficient on the radius of the plastic zone exists D ξ critical dynamic pressure coefficient. (3) The influence of intermediate principal stresses on the extent of the plastic zone and the magnitude of displacements in the pavement enclosure is inter-zonal in nature. The study on the evolution of the “butterfly-type” plastic zone is of great theoretical and practical significance for the development and utilisation of deep underground resources.